2023
DOI: 10.1210/jendso/bvad112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketogenic Diet on Reproductive Hormones in Women With Polycystic Ovary Syndrome

Karniza Khalid,
Saraswathy Apparow,
Irma Liyana Mushaddik
et al.

Abstract: Context Ketogenic diet has recently made a comeback as a part of lifestyle and dietary modifications in patients with polycystic ovary syndrome (PCOS). Despite studies suggesting its beneficial effects in reversing hormonal imbalance in women with PCOS, evidence has been patchy and derived from small populations under varying conditions. Objective To pool evidence from clinical trials to study the effects of ketogenic diet on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The authors concluded that VLCKD could improve metabolic and ovulatory dysfunction in patients with PCOS [95]. A recent review conducted by Khalid et al has confirmed the data just described, highlighting how a short-term ketogenic diet potentially improved hormonal imbalances commonly associated with PCOS [99].…”
Section: Nutritional Strategies For Pcosmentioning
confidence: 78%
See 1 more Smart Citation
“…The authors concluded that VLCKD could improve metabolic and ovulatory dysfunction in patients with PCOS [95]. A recent review conducted by Khalid et al has confirmed the data just described, highlighting how a short-term ketogenic diet potentially improved hormonal imbalances commonly associated with PCOS [99].…”
Section: Nutritional Strategies For Pcosmentioning
confidence: 78%
“…Among the different types of KD studies, VCKD can be considered an effective dietary intervention for the short-term treatment of patients with PCOS, as it rapidly leads to weight loss, with improvements in body composition and metabolic profile [94,96]. Specifically, the high-fat nutritional protocols proposed in the literature (such as KD) appear to provide benefits to patients with PCOS in terms of weight loss and control of metabolic parameters such as IR, glucose metabolism, lipid profile, and hormonal homeostasis [94,97,99]. Among the different types of KD studies, VCKD can be considered an effective dietary intervention for the short-term treatment of patients with PCOS, as it rapidly leads to weight loss, with improvements in body composition and metabolic profile [94,96].…”
Section: Discussionmentioning
confidence: 99%